Overt Coordination in Additive Numerals of Minority Languages in South China. (26th July 2017) - He, Chuansheng; Her, One‐Soon; Hu, Xiaoshi; Zhu, Weijing
Abstract: This paper explores a typology of overt coordination in additive numerals in a number of minority languages in South China. Among approximately 100 minority languages surveyed, 26 languages feature different coordinators for additive numerals and noun phrases. We show that these two types of coordinators are not semantically, etymologically, or morphologically related. This phenomenon presents a serious challenge to the proposal that additive numerals do not form constituents and that numeral coordination is derived from underlying nominal coordination in such languages.